2016
DOI: 10.3892/or.2016.5166
|View full text |Cite
|
Sign up to set email alerts
|

Angelicin inhibits human lung carcinoma A549 cell growth and migration through regulating JNK and ERK pathways

Abstract: Angelicin is a member of a well-known class of chemical photosensitizes that have anticancer proper-ties in several cancer cell lines. However, the effects and the potential underlying mechanisms of angelicin action on human lung cancer cells remain unclear. Here, we report that angelicin has an essential role in inhibiting human lung carcinoma growth and metastasis. We found that angelicin markedly induced cell apoptosis and arrested the cell cycle in vitro. Angelicin also inhibited the migration of non-small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…Mmp9 is regulated by NF-B signalling, which has been associated with poor prognosis in non-small cell lung cancers (25). Mmp9 inhibition has been reported to attenuate cancer cell invasion and metastasis (26,27). We found an increased expression of syndecan-2, NF-B (p65) and mmp9 in lung adenocarcinoma tissue ( Figure E2).…”
Section: Syndecan-2 Increases Mmp9 Expression and Activity And Is Assmentioning
confidence: 71%
See 1 more Smart Citation
“…Mmp9 is regulated by NF-B signalling, which has been associated with poor prognosis in non-small cell lung cancers (25). Mmp9 inhibition has been reported to attenuate cancer cell invasion and metastasis (26,27). We found an increased expression of syndecan-2, NF-B (p65) and mmp9 in lung adenocarcinoma tissue ( Figure E2).…”
Section: Syndecan-2 Increases Mmp9 Expression and Activity And Is Assmentioning
confidence: 71%
“…Mmp9, also known as gelatinase B, has been shown to play a prominent role in tumor malignant potential and lung-specific metastasis (23,35). Higher levels of mmp9 are correlated with poor patient prognosis in non-small cell lung cancer (36), and mmp9 inhibition has been reported to attenuate cancer cell invasion and metastasis (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…However, combined treatment angelicin (50–100 μM) and TRAIL (50 ng/mL) caused apoptotic cell death in Caki, Sk‐hep1, and MDA‐MB‐361 cells, but not normal cells. Li et al () also reported that angelicin inhibited growth and migration via regulation of JNK and ERK pathways. In our study, one mechanism of angelicin‐mediated TRAIL sensitization is down‐regulation of c‐FLIP expression.…”
Section: Discussionmentioning
confidence: 95%
“…Angelicin can induce apoptosis in neuroblastoma cells via the intrinsic caspase‐mediated pathway and modulation of apoptosis‐related genes (Rahman, Kim, Yang, & Huh, ). Angelicin suppresses proliferation of human lung carcinoma cells by promoting G2/M arrest and induction of apoptosis (Li et al, ). However, whether angelicin has sensitizing effects against TRAIL‐mediated apoptotic cell death is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the changes seen in the expression of apoptotic and anti-apoptotic proteins by angelicin is a positive indicator that angelicin has anticancer properties. Besides that, several different cells, such as promyelocytic leukaemia (HL-60), human lung cancer (A549), hepatoblastoma (HepG2), and hepatocellular carcinoma (Huh-7) cell lines, also yielded the same changes in the proteins mentioned above when incubated with angelicin for 24 or 48 h (Yuan et al, 2015;Li et al, 2016;Wang et al, 2017a). This shows that angelicin has the potential to be effective against multiple cancer cell lines.…”
Section: North America and Chinamentioning
confidence: 86%